Sex-related differences in profiles of muscle oxygen saturation of different muscles in trained cyclists during graded cycling exercise - Sendra-Pérez, C.; Priego-Quesada, J. I.; Salvador-Palmer, R.; Murias, J. M.; Encarnacion-Martinez, A. (Journal of Applied Physiology, 2023)
Although in recent years near-infrared spectroscopy has been used in many sports to monitor muscle oxygen saturation (SmO2), there is a lack of knowledge about the sex differences in SmO2 during exercise in different muscles. Our study aimed to examine SmO2 differences in muscles between female and male cyclists, during a graded cycling test and at the first and second lactate thresholds. Twenty-five trained cyclists and triathletes (15 males: 23 ± 7 yr, 1.78 ± 0.05 m, 70.2 ± 5.3 kg, and 10 females: 22 ± 5 yr, 1.64 ± 0.06 m, 58 ± 8 kg) performed a graded cycling test on the cycle ergometer. Power output and SmO2 in five muscles (dominant vastus lateralis, tibialis anterior, gastrocnemius medial, biceps femoris, and triceps brachii) were measured. Our mixed regression models showed that the interaction between power output and sex was significant for all the muscles analyzed (P < 0.001), indicating a greater decrease in SmO2 for males as power output increased. Moreover, the statistical parametric mapping analyses showed for females higher SmO2 in the middle of the test in biceps femoris (P = 0.03), gastrocnemius medial (P = 0.02), and tibialis anterior (P = 0.04). Finally, the males presented a lower SmO2 in all muscles where the second lactate threshold occurred, with greater evidence than in the first lactate threshold. In conclusion, females have higher SmO2 in all muscles, and these differences are more noticeable during the graded cycling test, such that males seem to have a greater reliance on oxygen extraction than females for a given relative intensity of exercise.